2020
DOI: 10.1177/1971400920975153
|View full text |Cite
|
Sign up to set email alerts
|

The role of diffusion tensor imaging in idiopathic normal pressure hydrocephalus: A literature review

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a syndrome that comprises a triad of gait disturbance, dementia and urinary incontinence, associated with ventriculomegaly in the absence of elevated intraventricular cerebrospinal fluid (CSF) pressure. It is important to identify patients with iNPH because some of its clinical features may be reversed by the insertion of a CSF shunt. The diagnosis is based on clinical history, physical examination and brain imaging, especially magnetic resonance imaging (MRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…In addition, the volume of the white matter of the brain was negatively correlated with the total score of the iNPHGS, suggesting that the more obvious the deformation of the white matter caused by pressure, the more severe the clinical symptoms. A study on iNPH using diffusion tensor imaging (DTI) found changes in the microstructure of the white matter of the brain, damage to the white matter axons around the ventricle, and gliosis ( 18 ). A DTI study also found corticospinal tract injury in patients with iNPH ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the volume of the white matter of the brain was negatively correlated with the total score of the iNPHGS, suggesting that the more obvious the deformation of the white matter caused by pressure, the more severe the clinical symptoms. A study on iNPH using diffusion tensor imaging (DTI) found changes in the microstructure of the white matter of the brain, damage to the white matter axons around the ventricle, and gliosis ( 18 ). A DTI study also found corticospinal tract injury in patients with iNPH ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cranial brain injury is a common neurosurgery traumatic disease, of which 70%~90% are mild to the brain injury, most of which are reversible forgetting, transient loss of consciousness, and other symptoms, which seriously affect the life, study, and work of patients [ 1 ]. However, due to the low positive rate of mild craniocerebral injury in skull, CT and conventional magnetic resonance imaging (MRI) examination and the lack of attention to neurosurgery, it is easy to cause the development of the disease and even lifelong disability.…”
Section: Introductionmentioning
confidence: 99%
“…Increased FA signal is reported as a prominent characteristic in NPH compared to other neurodegenerative diseases like AD or Parkinson's disease where FA is decreased. However, recent research reports decreased FA of the corticospinal tracts in NPH [60].…”
Section: Imagingmentioning
confidence: 89%